A 2‐year prospective analysis of insomnia as a mediator of the relationship between androgen deprivation therapy and perceived cognitive function in men with prostate cancer. Issue 24 (19th August 2021) - Garland, Sheila N.; Savard, Josée; Eisel, Sarah L.; Wassersug, Richard J.; Rockwood, Nicholas J.; Thoms, John; Jim, Heather S. L.; Gonzalez, Brian D.
Abstract : Background: Androgen deprivation therapy (ADT) may affect cognitive function in men with prostate cancer (PCa). This study examined whether insomnia symptoms mediate the relationship between ADT and perceived cognitive function and whether depressive symptoms, fatigue severity, and physical activity moderate the strength of this relationship. Methods: This was a prospective study of ADT recipients (n = 83) who were matched with control patients with PCa who were not on ADT (n = 92) and with controls with no history of cancer (n = 112) over a 2‐year follow‐up period. Perceived cognitive function and satisfaction were assessed with the Everyday Cognition Scale. Insomnia was assessed with the Insomnia Severity Index. Multilevel mediation analyses were conducted to estimate the indirect effect of ADT on perceived cognitive function through insomnia symptoms. Exploratory moderated mediation analyses assessed whether the indirect effect of ADT on perceived cognitive function through insomnia symptoms was dependent on levels of fatigue, depression, or physical activity. Results: Insomnia symptoms significantly mediated the relationship between receipt of ADT and perceived cognitive function ( P < .001) and satisfaction with cognition ( P < .001) after controlling for comorbidities. Men with greater fatigue had a more pronounced association of ADT with insomnia severity. Men with greater depressive symptoms had a stronger association between insomnia severity and worse perceived cognitive function. Physical activity was not a significant moderator of the relationship between ADT and perceived cognitive function. Conclusions: Insomnia influenced the relationship between ADT and perceived cognitive abilities. Interventions to address insomnia, fatigue, and depression may improve perceived cognitive function. Abstract : After adjustments for comorbidities, insomnia symptoms significantly mediate the relationship between receipt of androgen deprivation therapy and subjective cognition, which is moderated by fatigue and depression. Interventions to improve sleep, fatigue, and/or depression may also have a secondary effect of improving self‐appraisal of cognitive function.